2011
DOI: 10.1039/c0cp02183k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically controlled self-assembled monolayers characterized with molecular and sub-molecular resolution

Abstract: Self-assembled organization of functional molecules on solid surfaces has developed into a powerful and sophisticated tool for surface chemistry and nanotechnology. A number of reviews on the topic have been available since the mid 1990s. This perspective article aims to focus on recent development in the investigations of electronic structures and assembling dynamics of electrochemically controlled self-assembled monolayers (SAMs) of thiol containing molecules on gold surfaces. A brief introduction is first g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 163 publications
(240 reference statements)
1
47
1
Order By: Relevance
“…There have been many investigations on the characterization and manipulation of alkylthiol SAMs on noble metals and the properties of the interface have been included in a variety of reviews [3][4][5][6][7][8]. Recently, the interest in Au-thiol chemistry has been renewed due its relation to nanotechnology as it was discovered that alkylthiols are efficient stabilizing ligands for gold nanoparticles (AuNPs) [9].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many investigations on the characterization and manipulation of alkylthiol SAMs on noble metals and the properties of the interface have been included in a variety of reviews [3][4][5][6][7][8]. Recently, the interest in Au-thiol chemistry has been renewed due its relation to nanotechnology as it was discovered that alkylthiols are efficient stabilizing ligands for gold nanoparticles (AuNPs) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although proteins, 2629 peptides, 3040 and other biomolecules 41 assembled on surfaces have been imaged using the STM, distinguishing amino acid sidechain conformations in peptides adopting biologically relevant conformations ( i.e. , β sheets or α helices) has proven challenging.…”
Section: Introductionmentioning
confidence: 99%
“…To understand this complex interplay, it is essential to understand the interfacial properties of SAM-modified electrodes under electrochemical conditions. In this context, the influence of the electrode potential on formation kinetics [16, 17], structural properties [1820], and ionic permeability of SAMs has been subject to several works [19, 21]. Especially electrochemical desorption/readsorption studies revealed important details concerning the nature of the interfacial interactions between a chemisorbed monolayer and a metallic substrate, besides defining the applicable potential range for SAM-modified electrodes.…”
Section: Introductionmentioning
confidence: 99%